E-Learning Impact on Medical Students during COVID-19 Pandemic: Students’ Perspective - Yasmeen, Qamar (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objective To determine the satisfaction level, barriers, benefits, and challenges of medical students of Independent Medical College Faisalabad regarding online teaching during pandemic of COVID-19. Methodology This cross-sectional study was carried out from April 2021 to May 2021. In order to measure the satisfaction levels, barriers, benefits and challenge of eLearning of Independent Medical College Faisalabad medical students a web-based questionnaire consisting of 23 questions was generated using google form. Through various digital online platforms (E-mailing/E-messaging) the questionnaire form was shared with the participants. SPSS was used to analyze calculated data; presentation of data is carried in term of percentages (%) and frequencies (N). Results A total of 302 medical students participated in the study. The mean age of participants was 21.3 years. Among them 70.2% (n= 212) consist of male and 29.8% (n=212) were female. The majority of the participants (28.1%) were studying in 2nd-year MBBS. Among electronic device used for online study laptop was used as major electronic device (39.1%). The overall satisfaction index for respondents was 28.4%. Slow/weak internet connection was main challenge reported by 54% students. Conclusion Overall, there was dissatisfaction and negative comments regarding interaction among students, practical learning, focus on study, and technological/infrastructural flaws. Keywords: COVID-19, Online teaching, Satisfaction levels, Performance, Medical Student